Synthesis and Characterization of Thorium(IV) Metal Complexes with a Schiff Base - Arora, Kishore; Agarwal, D.D.; Goyal, R.C. (Asian Journal of Chemistry, 2010)
A series of new thorium(IV) complexes with a Schiff base derived from 2-amino pyridine, i.e., 2N-(benzalidene) aminopyridine (BAPy) has been synthesized. Analytical, conductance, mol. wt. and spectral data reveal that the complexes have the general composition ThX4·nL (X = NO3- or NCS-, n = 2; X = I-, n = 4 and X = ClO4-, n = 6; L = BAPy) Thorium(IV) atom is either 6 or 10-coordinated depending upon the anions present in these complexes.